Polyclinic Visitor Pattern Discovery Using Apriori Algorithm - Dharma, Teguh Satya; Suhartana, I Ketut Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Living in an information era, the presence of data is super important. With the data exponentially grows from decades to decades, it reflect the old saying that people today are so rich with data yet so poor on information. To dissect the information that contained within the large amount of data, a method is introduced called “Data Mining.” Data mining is a process of retriving a unique, unseen, and valuable information/insight from the data. Data mining comes with a lot of methods branches, one of those is pattern analysis, or also known as “Association Rules”. With the help of Association Rules, people can discover the relational pattern within the data, so people can make the best decision on the period of time. In this study, the writer is implementing Apriori Algorithm (one of the Association Rules algorithm) to see the pattern of a polyclinic visitor.